The Role of Gen Z in Reinforcing Pancasila Values Amidst Globalization - A. Achsanul Ikhtitam Wasom; Putri Wiji Lestari; Nadya NAhda Desyana; Irham Maulana (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study addresses the critical challenge of revitalizing Pancasila values among Generation Z (Gen Z) amidst rapid globalization. Globalization, while promoting access to information, simultaneously poses a threat to national identity and core values like collectivism and nationalism. The research aims to explore the strategic role of Gen Z in strengthening Pancasila through the framework of governance collaboration, involving public, private, and civil society sectors. Using a qualitative-descriptive literature review method , the study identifies three main areas where Gen Z can actively implement Pancasila values: (1) Strengthening Character Education by acting as innovators and developing digital content to teach the values of Divinity and Humanity; (2) Community Social Activities by coordinating Karang Taruna initiatives and practicing the values of Unity and Social Justice through Gotong Royong ; and (3) National Literacy Movement by promoting critical literacy, which forms the foundation for practicing Consultative Democracy (Sila IV). The results conclude that continuous collaboration transforms Pancasila from a theoretical concept into practical action, positioning Gen Z as the main pillar for maintaining national integrity in the digital era.